Mitigating the Adverse Effects of Lead and Cadmium Heavy Metals-Induced Oxidative Stress by Phytogenic Compounds in Poultry - Rohollah Ebrahimi; Mahdi Ebrahimi; Majid Shakeri (Poultry, 2023)
Environmental pollution has increased over the past few decades, posing serious risks to all biological systems, including the poultry sector. Oxidative stress in chickens caused by dietary, environmental, and pathological variables influences how well chickens perform as well as the quality of meat and eggs. Lead (Pb) and cadmium (Cd) are two examples of heavy metals that are harmful for chicken health. They can cause oxidative stress by increasing the production of reactive oxygen species (ROS) and reactive nitrogen species (RNS) and blocking antioxidants from protecting cells from increased amounts of free radicals. The oxidative state of heavy metals, their interactions with endogenous antioxidants, and chemical processes all affect how hazardous they are to the body. Today, scientists have investigated and applied a variety of nutritional tactics to lessen the harmful effects of oxidative stress on animal health brought on by heavy metals. Researchers have recently become interested in the chemicals because of their chelating and growth-stimulating functions, as well as the antioxidant qualities of useful plant components. The deleterious consequences of oxidative stress induced by two heavy metals on chickens is discussed in this review, along with phytogenic use as a potential intervention strategy to lessen these effects and maintain the redox equilibrium in poultry.